Trinuclear Ni(ii) oriented highly dense packing and π-conjugation degree of metal–organic frameworks for efficient water oxidation. Issue 39 (24th September 2019) - Zhai, Zhi-Min; Yang, Xiao-Gang; Yang, Zhao-Tong; Lu, Xiao-Min; Ma, Lu-Fang
Abstract : Trinuclear nickel cluster based MOF shows highly denser crystal packing and π-conjugation degree as well as outstanding OER performance with an overpotential of 270 mV at 10 mA cm −2 . Abstract : Oriented by the structure-directing effect of metal clusters, a novel trinuclear nickel-based MOF (Ni–BTC) exhibited highly denser crystal packing and π-conjugation degree, providing a platform for efficient charge carrier mobility between metal clusters through π-conjugated molecular bridges and long-term stability of an efficient oxygen evolution reaction.